DEVELOPMENT OF THE VILLAGE PROFILE WEBSITE AS AN INTEGRATED INFORMATION CENTER TO INCREASE COMMUNITY ACCESS TO INFORMATION - Prika Ayunda Lestari; Sanusi Sanusi; Virda Lantika; Zafira Khaulah Wahyu (Jurnal Abdisci, 2026)
Abstract Background. The development of information technology encourages digital transformation in government administration, including at the village level. However, information dissemination in Winong Village remains conventional and has not been integrated, as evidenced by the inactivity of the village website and the limited use of digital media. This leads to low accessibility, transparency, and effectiveness in delivering information to the public. Aims. This activity aims to design and develop a profile website for Winong Village to improve information accessibility, government transparency, and community services. Methods. This activity uses a descriptive qualitative method with a participatory approach. The activity was carried out in Winong Village as part of the Thematic Real Work Lecture (KKN) program for 40 days, from planning through evaluation. The data collection techniques used include observation, interviews, and documentation. Conclusion. The stages of implementing activities are carried out systematically, from identifying needs to designing systems, developing, testing, implementing, and evaluating. The result of this activity is the formation of a Winong Village profile website that contains important information, including village profiles, news, activities, and village potentials. This shows that a website can provide more structured, accessible information. The existence of the website also supports increasing transparency and efficiency in delivering information to the public. Implementation. Thus, the village website serves as an effective digital information medium for improving the quality of public services at the village level.